The Influence of Profitability, Liquidity and Leverage on Company Value With Dividend Policy as a Moderation Variable - Armela, Viska; Dewi, Meutia; Setianingsih, Dias (Fin Sinergy: Jurnal Manajemen Keuangan, 2024)
This research aims to determine the effect of profitability, liquidity and leverage on company value with dividend policy as a moderating variable in energy companies listed on the BEI in 2017-2021. The population in this study was all energy companies totaling 76 companies and the sample used was 10 companies using purposive sampling techniques. The data analysis methods used are multiple linear regression analysis, Moderated Regression Analysis, t test and coefficient of determination test. The research results show Y= 1.195 + 4.881X1 – 0.064X2 + 0.242X3. Based on the t test results, profitability, liquidity and leverage have a significant effect on company value. The results of Moderated Regression Analysis show that dividend policy is able to moderate the influence of profitability and liquidity on firm value, while dividend policy is unable to moderate the influence of leverage on firm value. The results of the coefficient of determination for the profitability, liquidity and leverage variables have an influence of 24.8% on company value, while the remaining 75.2% is influenced by other variables not examined in this research.